Validation of Recombinant Salivary Protein PpSP32 as a Suitable Marker of Human Exposure to Phlebotomus papatasi, the Vector of Leishmania major in Tunisia. - Soumaya Marzouki; Wafa Kammoun-Rebai; Jihene Bettaieb; Maha Abdeladhim; Saoussen Hadj Kacem; Rania Abdelkader; Sami Gritli; Jomaa Chemkhi; Hamide Aslan; Shaden Kamhawi; Afif Ben Salah; Hechmi Louzir; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:During a blood meal, female sand flies, vectors of Leishmania parasites, inject saliva into the host skin. Sand fly saliva is composed of a large variety of components that exert different pharmacological activities facilitating the acquisition of blood by the insect. Importantly, proteins present in saliva are able to elicit the production of specific anti-saliva antibodies, which can be used as markers for exposure to vector bites. Serological tests using total sand fly salivary gland extracts are challenging due to the difficulty of obtaining reproducible salivary gland preparations. Previously, we demonstrated that PpSP32 is the immunodominant salivary antigen in humans exposed to Phlebotomus papatasi bites and established that humans exposed to P. perniciosus bites do not recognize it. METHODOLOGY/PRINCIPAL FINDINGS:Herein, we have validated, in a large cohort of 522 individuals, the use of the Phlebotomus papatasi recombinant salivary protein PpSP32 (rPpSP32) as an alternative method for testing exposure to the bite of this sand fly. We also demonstrated that screening for total anti-rPpSP32 IgG antibodies is sufficient, being comparable in efficacy to the screening for IgG2, IgG4 and IgE antibodies against rPpSP32. Additionally, sera obtained from dogs immunized with saliva of P. perniciosus, a sympatric and widely distributed sand fly in Tunisia, did not recognize rPpSP32 demonstrating its suitability as a marker of exposure to P. papatasi saliva. CONCLUSIONS/SIGNIFICANCE:Our data indicate that rPpSP32 constitutes a useful epidemiological tool to monitor the spatial distribution of P. papatasi in a particular region, to direct control measures against zoonotic cutaneous leishmaniasis, to assess the efficiency of vector control interventions and perhaps to assess the risk of contracting the disease.